Organizational Sustainability and Green Practices – The Road Ahea - Kumar, Vijay (International Journal of Psychosocial Rehabilitation, 2020)
Green marketing refers to a technique how to sell products and services depending upon the accruing benefits related to environment. These types of products or services may be environment-friendly in one way or on the other side, can be manufactured and packed in an environment-friendly manner. Basic premise of this concept is consumers viewing “greenness’ of a product or service on the lines of merit and it creates a provision for purchasing choice. Consumers incline to pay some additional amount when buying green products in comparison to the alternative product. Likewise, Green HRM is using HRM practices to endorse resources in the durable way within the company and hence it promotes the reason of environmental sustainability. This paper focuses on the concept of integration of green practices of marketing and human resource management for attaining sustainability in the organization through different strategies and suggests certain measures for going green.